(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
After centuries of considerable isolation, the Opium Wars opened the Qing Empire to foreign presence. Westerners did not only establish some colonies, remarkably Hong Kong, but also managed to settle along the coast after the establishment of the treaty ports by the unequal treaties. Although China formally remained sovereign, the concessions and settlements implied the creation of foreign enclaves in which westerners, by the establishment of their own Courts and Municipal Councils, assured their jurisdiction and self-government. In this context, the treaty port of Shanghai clearly excelled by its prosperity and cosmopolitanism. The legal frame of its International Settlement is described in the following pages.